(untitled) (Journal of Atomic and Molecular Sciences, 2011)
We consider a double two-level system in which each single two-level system is driven by a strong linearly polarized pulse. The system is probed by a weak pulse orthogonally polarized. We study the distortion experienced by the probe temporal envelope when the relative phase between the pump and the probe is varied. We show that pulse behavior oscillates between two regimes that corresponds to transparency and amplification respectively. Interpretation of this effect is given within adiabatic representation.